Balanced bandpass filter based on magnetically coupled coplanar waveguide folded‐stepped impedance resonators. Issue 14 (1st July 2016) - Fernández‐Prieto, A.; Bhatker, J.; Lujambio, A.; Martel, J.; Medina, F.; Boix, R.R.
Abstract : A novel balanced differential bandpass filter implemented in coplanar waveguide (CPW) technology is presented. The filter is based on the use of two magnetically coupled CPW folded‐stepped impedance resonators. The use of magnetic coupling, instead of the more common electric coupling, provides inherent common‐mode rejection. Measured and simulated results demonstrate the benefits of the proposed balanced filter.